First records of Pyralis cardinalis Kaila, Huemer, Mutanen, Tyllinen & Wikström, 2020 in the Romanian fauna (Lepidoptera: Pyralidae) - Constantin Corduneanu; Ioan Surugiu; László Rákosy; Vlad Dinca (SHILAP)
Pyralis cardinalis Kaila, Huemer, Mutanen, Tyllinen & Wikström, 2020, was recently described based on material originating from northern Europe to South Korea and Japan. Here this species is reported for the first time from various localities in north-eastern Romania, where it can occur in sympatry and synchrony with the morphologically similar P. regalis ([Denis & Schiffermüller], 1775). Adult external morphology, male genitalia and DNA barcodes of Romanian specimens are examined. To the best of our knowledge, the Romanian specimens represent the southernmost confirmed records of P. cardinalis in Europe and highlight the need to better document the distribution of this taxon.